ANALISIS KEBIJAKAN LUAR NEGERI PRESIDEN DONALD TRUMP TERHADAP PENJUALAN SENJATA KE ARAB SAUDI - Syafira Khairani; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
As soon as US President inauguration, Donald Trump shows transactional foreign policy style on how US dealing with Saudi arms sales and conducting arms deal worth US110 billion. Yet, this arms sale poses several criticisms on its effect toward human rights issue. This research aims to analyze the role of Trump and closest advisers that might take part inventing the policy to maintain arms sales to Saudi.By using theoretical framework by Irving Janis on Groupthink, this research explores how policy conducted by the role of small-groups among US foreign policy makers. The research method used is qualitative with and descriptive type of research. Technique of data collection come from several sources such as official government documents, books, academic journals and credible news sites.This research came into several findings. First, the majority of Republican Senators and veto power by the US President has benefiting Saudi arms deal. Second, there is also the involvement of interest groups from the defense industry who lobbied policies. Third, according to Hermann's explanation, Trump is a dominant type of leader and a ‘crussader’, thus shaping the decision-making process that supports his own preferences. Lastly, arms sales policy was driven by the impetus from small groups (groupthink), particularly senior adviser Jared Kushner. The group's norms of unanimity to continue arms sales are also influenced by the perception of the dominant leader that ease him to make decisions despite political constraints in the US foreign policy structure. Keywords: Donald Trump, Foreign Policy Analysis, Arms Sales, Groupthink, United States, Saudi Arabia.